Spectral Properties and Finite Pole Assignment of Linear Neutral Systems in Banach Spaces. (15th June 2010) - Xia, Xuewen; Liu, Kai
Abstract : We will consider a pole assignment problem for a class of linear neutral functional differential equations in Banach spaces. We will think of the neutral system studied as that of involving no time delays and reduce the study of adjoint semigroups and spectral properties of neutral equations to those of Cauchy problems. Under the assumption that both the control and eigenspace of pole are finite dimensional, we establish the rank conditions for finite pole assignability.